“The Subaltern Ethnographer: Blurring the Boundaries through Amitav Ghosh’s Writing” - Martos Hueso, María Elena (Miscelánea: A Journal of English and American Studies, 2007)
This study aims to interpret Amitav Ghosh’s works as an alternative positioning within the post-colonial debate. His role as an ethnographer is particularly outstanding in this respect, and I may go as far as to suggest the figure of Calcuttaborn novelist Amitav Ghosh as incarnating the role of the subaltern anthropologist who is able to effectively contest the traditional discursive practices inspired by orientalist ethnography. Two parallel strategies will be used to achieve this objective: (1) turning ethnographic discourse from “a discourse that narrativizes” into “a discourse that narrates”, in the direction of Hayden White’s The Content of the Form; and (2) revitalising the “anthropological spirit” within Benedict Anderson’s definition of the nation as an “imagined political community”. To that purpose we will examine two relevant works in Ghosh’s early writings, The Shadow Lines (1988) and In an Antique Land (1992), as examples of the implementation of “thick description” in both literary and non-fictional texts. Ghosh’s overall strategy is to “write back to the centre” through means other than metafiction, parody or the Bakhtinian carnivalesque —i.e., strictly literary devices widely popular in current post-colonial fiction— and use the practices of contemporary anthropology —traditionally associated with Empire— in the construction of subaltern identity.
Keywords: Amitav Ghosh; The Shadow Lines; In An Antique Land; Subaltern; Post-colonial